Factors associated with physical inactivity among first-year undergraduate students of Universiti Putra Malaysia - Mohammed, Goje (2014)
Globally physical inactivity causes about 2 million preventable deaths per annum and it has been associated with increasing morbidity and mortality of cardiovascular and other non–communicable diseases. The prevalence of physical inactivity among Malaysian adults aged 18 years and above is 43.7%. The prevalence of physical inactivity among American college students was 16.7, the prevalence is 8.0% among Malaysian students and 15% among undergraduate students of Universiti Putra Malaysia (UPM). The purpose of this study is to identify the factors associated with physical inactivity among first year undergraduate students of UPM. A crosssectional study was conducted in 2013 among 1135 first year undergraduate students of UPM using a cluster sampling. Data was collected between September and November 2013 using self-administered questionnaire. The data was analysed using descriptive, bivariate and multivariate data analysis by SPSS version 21. The response rate was 72.3%. Majority of the respondents were females (77.4%), Malay ethnic group (79.5%) and respondents age is 18 to 25 years. Total family income ranges from RM500.00 to RM 16,000.00. The findings revealed that the prevalence of physical inactivity among the respondents was 41.4%. The result further showed that there was a significant association between gender, family income, respondents who do not believe that student in their college are active, self-efficacy of physical activity, mental health, body image perception with physical inactivity. The independent factors for physical inactivity were females (AOR=4.3, 95% CI: 2.66,7.24); those with family income < RM 2,500.00 (AOR=4.1, 95% CI: 2.98,5.90); respondents who do not believe that student in their school are active (AOR=1.8, 95% CI: 1.22,2.88); respondents with mental health probable cases (AOR=1.6, 95% CI: 1.15,2.31); low self-efficacy (AOR=1.7, 95% CI: 1.26,2.50); respondents who are currently overweight or obese (AOR=1.5, 95% CI: 1.01,2.28). In conclusion, the prevalence of physical inactivity among first year undergraduate students of UPM is high. Intervention to reduce the prevalence of physical inactivity should be targeted on modifiable factors such as improving self-efficacy to do physical activity, counselling to reduce mental health problems and encouragement in the use of UPM bicycle recently introduce in the campus.